PERAN DINAS KOPERASI, USAHA KECIL DAN MENENGAH DALAM PENGEMBANGAN PELAKU USAHA MIKRO KECIL MENENGAH - Farismah Agustin, Isnaeni; Fadil, Muhammad (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Indonesia is a country in the developing category characterized by the government's main activity, namely national development. The economic sector's position is very much considered in national development in Indonesia. The economy is still turbulent, making people feel that their lives are increasingly difficult. The development of today's times affects the increasing demands of society for its way of life, and the way of thinking of society is becoming more modern, conceptualized, sophisticated, and complex. Bekasi City Small and Medium Enterprises Cooperative with MSME development based on the 2018-2023 Strategic Plan. The Bekasi City Government has broader authority in designing and implementing every policy at the regional level except for matters determined to be central and provincial authorities. Efforts to encourage development in Bekasi City to achieve the Vision and Mission of Bekasi City are complex and cannot be implemented using partial and sectoral management approaches. The results of research at the City Small and Medium Enterprises Cooperative Office with data collection methods, observation, interviews, and documentation techniques can be concluded that they are still not running optimally.